McGraw-Hill's GMAT : - Hasik, James (McGraw-Hill, 2006)
Before you apply to today's top business schools, you need to develop a solid set of strategies that will raise your GMAT score-and your chances for success. This all-in-one guide from the nation's leading test-preparation experts covers the full range of subjects you'll encounter on the GMAT, including math, syntax, and logic, with a special emphasis on the crucial quantitative questions. You'll learn how the new computerized exams are administered and scored, and get the preparation tools, test-taking techniques, and high-scoring secrets of professional tutors.